1998
DOI: 10.1172/jci4619
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal role of TARC, a CC chemokine, in bacteria-induced fulminant hepatic failure in mice.

Abstract: Thymus and activation-regulated chemokine (TARC) is a recently identified lymphocyte-directed CC chemokine which specifically chemoattracts T helper type 2 CD4 ϩ T cells in human. To establish the pathophysiological roles of TARC in vivo, we investigated whether a monoclonal antibody (mAb) against TARC could inhibit the induction of hepatic lesions in murine model using Propionibacterium acnes and lipopolysaccharide (LPS). P . acnes -induced intrahepatic granuloma formation in the priming phase is essential to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
147
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(150 citation statements)
references
References 30 publications
(40 reference statements)
3
147
0
Order By: Relevance
“…It is a CCR4 ligand that attracts primed CD4 ϩ T cells, 64 in particular IL-4-producing T cells. 65 Interestingly, TARC is up-regulated by both IL-4 and IFN-␥ in bronchial epithelial cells, and a maximum production occurred with combination of TNF-␣, IL-4, and IFN-␥. 66 Our findings now suggest a common role in granuloma formation.…”
Section: Discussionmentioning
confidence: 92%
“…It is a CCR4 ligand that attracts primed CD4 ϩ T cells, 64 in particular IL-4-producing T cells. 65 Interestingly, TARC is up-regulated by both IL-4 and IFN-␥ in bronchial epithelial cells, and a maximum production occurred with combination of TNF-␣, IL-4, and IFN-␥. 66 Our findings now suggest a common role in granuloma formation.…”
Section: Discussionmentioning
confidence: 92%
“…The expression profile of chemokines in the skin lesion showed increased expression of TARC, eotaxin 2, and CC chemokine receptors even in STAT6 Ϫ/Ϫ NC mice. The TARC/MDC-CCR4 system has been shown to be involved in the Th2-mediated disease process (37,38). However, consistent with the observation in NC mice that IFN-␥, but not IL-4, induces TARC expression in keratinocytes (15), our results indicate that the enhancement of TARC expression at the pathological site correlated with the increased IFN-␥ expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent reports demonstrated that transgenic mice expressing caspase 1 in keratinocytes spontaneously developed AD-like skin disease with an elevation of the active form of IL-18 in serum (37). Recent linkage analysis demonstrated that the locus responsible for skin disease in NC mice is on chromosome 9, and the IL-18 gene is near the locus (42).…”
Section: Discussionmentioning
confidence: 99%
“…Hamster anti-mouse TARC mAb 5H5 was prepared as described previously (23,24). The specificity of this Ab was evaluated by 1) binding assay using ELISA, 2) calcium mobilization assay, and 3) chemotaxis assay as described below.…”
Section: Reagentsmentioning
confidence: 99%